Foliar image-based characterization of airborne particulate matter in an urban area and its implications for remediation - Ankesh Tiwari; Triratnesh Gajbhiye; Mohineeta Pandey; Kajal Agrawal; Shuvadarshini Naik; Shubhrasmita Meher; Dinesh Patel; Rashmi Dubey; Tanzil Gaffar Malik; Mohammed Zari; Ali Zari; Khalid M Alghamdi; et al. (Scientific Reports)
Abstract This study addresses the pervasive issue of particulate matter (PM) emission in urban areas, proposing a better approach using scanning electron microscope (SEM) techniques to identify plant species effective in airborne PM removal. Conducted in Bilaspur city, the research strategically selected six plant species across four distinct sites and applied the SEM-Image J method for analysis, yielding significant insights, especially in the respirable PM range. Among the tested plant species, Senna Siamea and Dalbergia Sissoo emerged as consistent and standout performers, displaying the highest PM removal efficiency across all sites. Notably, the smaller leaves of Senna siamea and Dalbergia sissoo prevent PM from being resuspended in the air by strong winds, enhancing their overall performance in combating PM pollution. The SEM-EDS analysis was then employed for morphological and chemical characterizations of the PM, revealing anthropogenic sources as the primary contributors to pollution. Hazardous elements, including arsenic (As), antimony (Sb), iron (Fe), indium (In), terbium (Tb), chlorine (Cl), and iodine (I), were identified, underscoring potential health risks associated with the PM composition. The study underscores the significance of SEM-EDS based plant selection for mitigating airborne PM pollution and improving air quality. Senna Siamea and Dalbergia Sissoo are identified as top choices for effective PM removal, marking a significant step towards sustainable urban environments. The findings contribute valuable insights into the chemical makeup of PM, facilitating a deeper understanding of its sources and potential health implications. Overall, this research serves as a crucial step in developing strategies to combat air pollution and fosters the creation of healthier and more sustainable urban environments.